Draft Annual Plan 1986-87 Scheme Details Volume-II Government of Manipur - Planning Commission (Planning Commission, 1985)
Based on the experience of Blanket allocation of 500 farming families irrespective of hills. & valley to one VEW for the last 5 years, the necessary of reducing the number of farming families in the hill districts is felt needed to compensate the loss of efficiency on the-part of functionaries due_to transport bottleneck and sparsely located Villages.
Planning Department, Govt. of Manipur